Respuesta :
When x=0, f(0) = 3 and g(0) = 6
Then
The y-intercept of g(x) is equal to 2 times the y-intercept of f(x)
Then
The y-intercept of g(x) is equal to 2 times the y-intercept of f(x)
Answer:
The y-intercept of g(x) is equal to 2 times the y-intercept of f(x)
Step-by-step explanation:
The functions f(x) and g(x) are described using the following equation and table
[tex]f(x)=3(1.02)^x[/tex]
x : -1 0 1 2
g(x) : -4 6 8 10
f(x) : 2.94 3 3.06 3.12
We need to compare the y-intercept of f(x) and g(x)
As we know the y-intercept of any function when x=0.
First we find the y-intercept of f(x) and g(x), f(0) and g(0)
y-intercept of g(x), g(0) = 6
y-intercept of f(x), f(0) = 3
6 is 2 times of 3.
Therefore, The y-intercept of g(x) is equal to 2 times the y-intercept of f(x)